Comparison between Acrylic Hydrophilic and Acrylic Hydrophobic Intraocular Lens after Phacoemulsification - Furrukh Ahmed, Riaz Ahmed, Imran Ghayoor, M Mubassher Malik, Ghazala Tabssum (Pakistan Journal of Ophthalmology, 2011)
Purpose: To compare the results of acrylic hydrophilic and acrylic hydrophobic Intraocular lenses in terms of visual acuity (VA), behavior of eye (Uveitis) and posterior capsular opacification (PCO). Material and Method: The study was carried out from September 2004 to October 2005 in the department of ophthalmology Liaquat National Hospital Karachi. One hundred patients were included in the study and were equally divided in two groups. All patients underwent Phacoemulsification with IOL implantation (50 patients hydrophilic IOL and 50 hydrophobic IOL). Results: 96% had VA of 6/12 or better unaided or with refraction, 2% developed posterior capsule thickening, whereas, none of the patients developed Uveitis after one year. Conclusion: There was no significant difference between two IOLs regarding VA, Uveitis and PCO after one year follow up. There was no effect of biomaterial on PCO.